1978
DOI: 10.1111/j.1751-1097.1978.tb07668.x
|View full text |Cite
|
Sign up to set email alerts
|

“Sunlight”‐induced Mammalian Cell Killing: A Comparative Study of Ultraviolet and Near‐ultraviolet Inactivation

Abstract: Abstract— We have examined the relationship between the survival curves obtained with UV light (254 nm) and those obtained with a near‐UV sburce (Westinghouse Sun Lamps, FS20) simulating sunlight for cultured Chinese hamster cells, C3H mouse cells, and HeLa cells. In no case do the “sunlight” survival curves have the same shape as the UV survival curves. Also, the combined lethal effects of UV and near‐UV, sunlight‐like exposures are not entirely additive. Hence, we conclude that (1) the cell‐killing photolesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The results presented in Figure 1 indicate that 2-aminofluorene is also activated to a mutagen by light. The activation of 2-aminofluorene using a sun lamp, which emits wavelengths of light primarily below 350 nm [23], confirms the observations of DeFlora [5]. The activation seen using the black, blue, and coolwhite lamps indicates that lamps emitting wavelengths of light longer than those produced by the sun lamp are also effective in the mutagenic activation of this compound.…”
Section: Discussionsupporting
confidence: 83%
“…The results presented in Figure 1 indicate that 2-aminofluorene is also activated to a mutagen by light. The activation of 2-aminofluorene using a sun lamp, which emits wavelengths of light primarily below 350 nm [23], confirms the observations of DeFlora [5]. The activation seen using the black, blue, and coolwhite lamps indicates that lamps emitting wavelengths of light longer than those produced by the sun lamp are also effective in the mutagenic activation of this compound.…”
Section: Discussionsupporting
confidence: 83%
“…Cyclobutane pyrimidine dimers were one of the main lesions produced after 254 nm UV [Setlow, 19681, and individuals afflicted with the disease xeroderma pigmentosum were sensitive to killing and mutation by UV [Maher and McCormick, 10761, and were defective in their ability to excise dimers [Cleaver, 1975;Setlow et al, 19691 and (6-4) photoproducts [Mitchell and Narin, 19891. Although lesions other than pyrimidine dimers (e.g., ( 6 4 ) photoproducts, thymine glycol, thymine-thymine adducts and their dehydration products, single strand breaks, alkali-labile bonds, DNA-DNA and DNA-protein cross links) were thought also to be responsible for the biological effects of SL in mammalian cells [Cleaver et al, 1988;Elkind et al, 1978;Hariharan and Cerutti, 1977;Smith and Paterson, 1981;Zelle et al, 19801, other work on human [Kantor and Setlow, 19821, frog [Rosenstein and Kantor, 198 I], Chinese hamster V-79 [Rothman and Setlow, 19791, and fish cells [Shima et al, 1981;Shima and Setlow, 19841 have shown that the mechanism of cell killing, at wavelength < 3 15 nm. is mainly the formation of pyrimidine dimers, as was observed for 254 nm.…”
Section: Discussionmentioning
confidence: 99%
“…has been studied extensively. Reports on the cytotoxic (Elkind et al, 1978), mutagenic (Hsie e f al., 1977), and oncogenic (Blum, 1959) effects of U V have been widely reported (Setlow, 1978). Many earlier studies employed "germicidal" lamps as the source of U V (eg, Cleaver, 1968).…”
Section: Introductionmentioning
confidence: 99%